Implementation of the Independent Learning Curriculum Policy at MAN 2 Langkat - Muammar Muammar; Candra Wijaya; Yusuf Hadijaya (South Sulawesi Education Development (SSED), 2024)
This research aims to investigate the implementation of the Independent Learning Curriculum policy at MAN 2 Langkat. The study is a policy research project utilizing a qualitative approach. The subjects of this research include the head of the madrasa, the deputy head of the madrasa for curriculum affairs, the curriculum development team, and teachers. Data collection techniques include interviews, documentation, and observation. Data analysis is conducted interactively, encompassing data reduction, data presentation, and verification/conclusion drawing.The results of this study indicate that: 1) Problem Structuring, The issues related to the implementation of the Independent Learning Curriculum policy at MAN 2 Langkat are addressed through various approaches, including the evaluation of infrastructure, perspectives of teachers and students, funding, and parental support. Identified problems include low reading interest and a lack of resources and facilities. 2) Monitoring, The monitoring of the implementation of the Independent Learning Curriculum policy at MAN 2 Langkat is conducted periodically and systematically to identify progress and potential obstacles that may arise during the implementation process. 3) Evaluation, The evaluation of the implementation of the Independent Learning Curriculum policy at MAN 2 Langkat is emphasized by the head of the madrasa. Key aspects of evaluation include monitoring curriculum implementation, stakeholder involvement, data analysis, and the impact on achieving educational goals. The evaluation process is conducted in stages, involving teachers, the head of the madrasa, and external parties such as the Head of the Religious Affairs Office and the Department of Religion.